Markedsliberalistiske forskyvninger i det psykiske helsefeltet – om forholdet mellom politisk styring og faglig disiplinering - Karlsson, Bengt (Nordisk tidsskrift for helseforskning, 2015)
Since 1998, there has been several extensive reforms in the mental health field in Norway. The reforms have changed the basic politics and conditions for the development of the field and set out a new framework for the different actors’ participation. There are tensions in the development of the field with different strategies focusing on demands for change and better quality in the services. The reforms highlights different aspects of leadership and management through control, power and knowledge, discipline and self-discipline. The change of services also require ways to change the professionals and the citizens’ different identities. The ways they collaborate and relate to one another are being standardized and often experienced as depersonalized. Meanwhile, both the service users and the professionals are involved in the governance and thus have a decisive influence on the success of the changes. This is a disciplinarian of the professionals into practices based in neoliberal thinking rather than based in professionals’ knowledge from experience and practice. Many professionals experience their autonomy as reduced and threatened. They are being forced into a certain ways of organizing and practicing their work.